History of Romanian Medical Informatics: Learning from the Past to Reshape the Future - Mihalas, George I.; Stoicu-Tivadar, Lacramioara (Yearbook of Medical Informatics, 2018)
Objectives: The paper presents a review of the history of medical informatics in Romania, starting from the pioneering works, relating the present, and foreseeing the future.Methods: Major milestones of the development of this field have not been simply enumerated, but described within the specific socio-political frame, grasping the entire context over the last four decades in Romania. Two main perspectives have been traced: education and training in medical informatics and implementations in healthcare.Results: Four distinctive historical periods are identified and the major events of each period are described in a critical manner. The history of the Romanian Society of Medical Informatics is presented in a separate chapter. The last section is dedicated to the present state of the field in Romania.Conclusion: The history of Romanian Medical Informatics spans many years and is rich in content. The Romanian Society of Medical Informatics is mainly the result of the efforts undertaken by an enthusiastic and sound professional community, trying to continue the tradition, to achieve new goals, and to work as an active member of the international biomedical/health informatics community.
Keywords: Medical Informatics/history; technology development; education; health information systems; Romania